Epithelial NSD2 maintains FMO‐mediated taurine biosynthesis to prevent intestinal barrier disruption - Yue Xu; Xiuying Xiao; Chunxiao Ma; Ziyi Wang; Wenxin Feng; Hanyu Rao; Wei Zhang; Ningyuan Liu; Rebiguli Aji; Xiangjun Meng; Wei‐Qiang Gao; Li Li (Clinical and Translational Medicine)
Abstract Background Inflammatory bowel disease (IBD) presents a significant challenge due to its intricate pathogenesis. NSD2, a histone methyltransferase responsible for dimethylating histone 3 at lysine 36, is associated with transcriptional activation. NSD2 expression is decreased in both the intestinal epithelial cells (IECs) of IBD patients and the IBD mouse model. However, the precise role of NSD2 in IBD remains unexplored. Methods Colon tissues from IBD mice, SW620 cells and MC38 cells, were used as research subjects. Clinical databases of IBD patients were analysed to investigate whether NSD2 expression is reduced in the occurrence of IBD. NSD2‐knockout mice were generated to further investigate the role of NSD2 in IBD. The IECs were isolated for RNA sequencing and chromatin immunoprecipitation sequencing to identify molecular signalling pathways and key molecules leading to IBD in mice. Molecular and cellular experiments were conducted to analyse and validate the role of NSD2 in the development of IBD. Finally, rescue experiments were performed to confirm the molecular mechanism of NSD2 in the development of IBD. Results Deficiency of NSD2 in mouse IECs aggravated epithelial barrier disruption and inflammatory response in IBD. Mechanistically, NSD2 loss led to downregulation of H3K36me2 and flavin‐containing monooxygenase (FMO) (taurine‐synthesis enzyme) mRNA, resulting in decreased taurine biosynthesis in IECs. Significantly, supplementation with taurine markedly alleviated the symptoms of NSD2 deficiency‐induced IBD. Conclusions These data demonstrate that NSD2 plays a pivotal role in maintaining FMO‐mediated taurine biosynthesis to prevent intestinal inflammation. Our findings also underscore the importance of NSD2‐H3K36me2‐mediated taurine biosynthesis in maintaining intestinal mucosal barrier homeostasis. Key points In this study, we investigated the role of the histone methyltransferase NSD2 in preventing intestinal barrier disruption by sustaining taurine biosynthesis. NSD2 levels were reduced in both human specimens and mouse models of IBD. We demonstrate that NSD2 loss hinders the process of taurine synthesis in intestinal cells, leading to increased intestinal inflammation. Supplementation with taurine significantly relieved the symptoms caused by NSD2 deficiency. These data suggest that maintenance of NSD2‐mediated taurine biosynthesis is vital for preserving the intestinal barrier and attenuating inflammation.